Analysis of the Service System to Raise Awareness of Mandatory Inspection and Re-Inspection at the Malang City Legal Metrology Unit - Fifi Irmawati; Prima Vitasari Vitasari; Renny Septiari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research analyses how the service system influences mandatory verification awareness at Malang City's Legal Metrology Unit. Despite the elimination of service fees in 2024, fluctuations in compliance (2021–2024) indicate that cost alone does not drive participation; service system aspects play a significant role. This research employs a quantitative approach using a survey method. The population consists of 1,324 traders who had not conducted verification or re-verification in four traditional markets in Malang City. A total of 307 respondents were selected using proportional stratified random sampling. The independent variables include accessibility, availability, service quality, efficiency, and effectiveness, while the dependent variable is mandatory verification awareness. Data were collected through questionnaires, interviews, observations, and documentation. Data analysis techniques included validity and reliability testing, descriptive analysis, partial t-tests, and simultaneous F-tests. The results indicate that all research instruments are valid and reliable. Descriptively, accessibility is categorised as good (mean = 3.824), availability as moderately good (mean = 3.188), and service quality as moderate (mean = 3.015). These findings suggest that improvements are particularly needed in the dimensions of accessibility, availability, service quality, efficiency, and effectiveness. Simultaneously, the service system has a significant effect on mandatory verification awareness. Therefore, enhancing the service system through improved information access, optimisation of human resources, strengthening of staff competence, and increased service efficiency and effectiveness can serve as strategic measures to raise mandatory verification awareness and achieve measurement orderliness in Malang City.